FDZ data description: Smaragd-survey - Lukas Hörnig; Sandra Schaffner (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
This report gives a short description of the data set Smaragd-Survey. The data have been collected by a commercial market research institute, infas360. Infas360 conducts online surveys several times a year with about 10,000 participants. These surveys are distributed as "Casa Monitor" and focus on changing focus topics. The Smaragd-Survey is a subset of the Casa Monitor, i.e. three surveys which were conducted between February 2021 and January 2022. The questions cover experiences of the respondents with the Covid-19 pandemic, especially work from home and attitudes towards Covid-19 vaccination. This report describes the resulting data set in more detail. – – Diese Datenbeschreibung gibt eine kurze Übersicht über den Datensatz Smaragd-Survey. Die Daten wurden von einem kommerziellen Marktforschungsinstitut, der infas360, erhoben. Infas360 führt mehrmals im Jahr Online-Umfragen mit rund 10.000 Teilnehmern durch. Diese Umfragen laufen als "Casa Monitor" und behandeln wechselnde Schwerpunktthemen. Die Smaragd-Umfrage ist ein Auszug des Casa Monitors, d.h. drei Umfragen, die zwischen Februar 2021 und Januar 2022 durchgeführt wurden. Die Fragen umfassen die Erfahrungen der Befragten mit der Covid-19-Pandemie, insbesondere die Arbeit von zu Hause aus und die Einstellung zur Covid-19-Impfung.
Keywords: 330